Letter : Basque Children's Homes - Cooper, James
038-0135-001 REGISTERED OFFICE:1 BALLOON ST. MANCHESTER, 4. TELEGRAPHIC ADDRESS:"WHOLESALE,"E.D.O. LONDON. TELEPHONE: ROYAL 7221 EXTENSION NO. PLEASE ADDRESS YOUR REPLY CO-OPERATIVE WHOLESALE SOCIETY LIMITED, BRANCH ADMINISTRATIVE OFFICE, 99, LEMAN STREET, LONDON, E.1. Our reference: - A - Your reference: HVT/FC/461. 23rd June 1938. Dear Mr. Tewson, BASQUE CHILDREN'S HOMES. We beg to acknowledge receipt of your letter of the 21st inst., and - in the absence of Mr. Newman on holiday - we are giving the matter our best attention. Yours faithfully, pro Society, Jas Cooper Mr. H. Tewson, Assistant Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. 292/946/38/135(I)